Electrochemical etching of α-cobalt hydroxide for improvement of oxygen evolution reaction. Issue 24 (3rd June 2016) - Liu, Peng Fei; Yang, Shuang; Zheng, Li Rong; Zhang, Bo; Yang, Hua Gui
Abstract : Electrochemically etched α-Co(OH)2 –Cl, due to the dechlorination-induced defective structures and in situ formation of CoOOH fragments, are highly active for OER. Abstract : Exploring low-cost and high-efficiency electrocatalysts for oxygen evolution reaction (OER) is of paramount importance to develop large-scale alkaline water-splitting electrolyzers (AWEs). Cobalt-based materials have been widely studied because of their promising activity and abundance. However, exposing more active sites for cobalt-based electrocatalysts with enhanced activity and durability still remains as a great challenge. Herein, we demonstrate that chlorine intercalated α-type cobalt hydroxide can be electrochemically etched to form a highly active OER catalyst, achieving a current density of 10 mA cm −2 at an OER overpotential of ∼320 mV. The improvement in the OER activity can be ascribed to the dechlorination induced defective structures and in situ formation of cobalt oxyhydroxide fragments as active sites via anodic polarization. Our findings suggest a novel strategy of electrochemical etching of chlorine containing hydroxide catalysts to obtain defective oxyhydroxides for continuous electrochemical water splitting.